Stemness, Pluripotentiality, and Wnt Antagonism: sFRP4, a Wnt antagonist Mediates Pluripotency and Stemness in Glioblastoma - Bhuvanalakshmi, G.; Gamit, N.; Patil, M.; Arfuso, Frank; Sethi, G.; Dharmarajan, Arunasalam; Kumar, A.; Warrier, S. (MDPI AG, 2019)
Background: Chemotherapeutic resistance of glioblastoma has been attributed to a self-renewing subpopulation, the glioma stem cells (GSCs), which is known to be maintained by the Wnt β−catenin pathway. Our previous findings demonstrated that exogeneous addition of the Wnt antagonist, secreted fizzled-related protein 4 (sFRP4) hampered stem cell properties in GSCs. Methods: To understand the molecular mechanism of sFRP4, we overexpressed sFRP4 (sFRP4 OE) in three human glioblastoma cell lines U87MG, U138MG, and U373MG. We also performed chromatin immunoprecipitation (ChIP) sequencing of sFRP4 OE and RNA sequencing of sFRP4 OE and sFRP4 knocked down U87 cells. Results: We observed nuclear localization of sFRP4, suggesting an unknown nuclear role. ChIP-sequencing of sFRP4 pulldown DNA revealed a homeobox Cphx1, related to the senescence regulator ETS proto-oncogene 2 (ETS2). Furthermore, miRNA885, a p53-mediated apoptosis inducer, was upregulated in sFRP4 OE cells. RNA sequencing analysis suggested that sFRP4-mediated apoptosis is via the Fas-p53 pathway by activating the Wnt calcium and reactive oxygen species pathways. Interestingly, sFRP4 OE cells had decreased stemness, but when knocked down in multipotent mesenchymal stem cells, pluripotentiality was induced and the Wnt β-catenin pathway was upregulated. Conclusions: This study unveils a novel nuclear role for sFRP4 to promote apoptosis by a possible activation of DNA damage machinery in glioblastoma.